Double-effect carbon clamping cloth with regeneration function for air purifier and preparation method of double-effect carbon clamping cloth
By using the preparation method of a dual-effect carbon clamp in the air purifier, the combination of the exothermic framework layer and the activated carbon layer is used to realize the regeneration function of the air purified material, and the problem of failure after adsorption and saturation in the prior art is solved. , improves purification efficiency and material regeneration rate.
Patent Information
- Application Number
- CN202411562429.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing air purifier fails after adsorption saturation and needs to be replaced regularly, and may cause secondary pollution to the use environment, making the material regeneration function impossible.
Using the preparation method of double-effect carbon clamping cloth, by calcining TiO2, K2CO3 and La(NO3)3 and immersing it, an exothermic framework layer is formed, and an activated carbon layer and a hot melt adhesive web film are laid thereon, and a catalytic layer is used. Exothermic reaction realizes material regeneration, reduces heat conduction loss, and improves regeneration rate.
It realizes the regeneration function of air purification materials, is convenient to operate, is green and environmentally friendly, improves the regeneration rate and adsorption capacity, reduces cost and filtration resistance, and enhances the hardness and adsorption efficiency of the material.
Smart Images

Figure CN119186188A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air purification, and in particular to a double-effect carbon-containing cloth for an air purifier with a regeneration function and a preparation method thereof. Background Art
[0002] Adsorption is the process of treating a gas mixture with a porous solid adsorbent so that one or several components are adsorbed on the solid surface to achieve separation. Since the adsorbent has high selectivity and high separation effect, it can separate mixtures that are difficult to separate by other methods, effectively remove pollutants with very low concentrations, and has high purification efficiency, simple equipment, and convenient operation. It is particularly suitable for the purification of gaseous pollutants such as volatile organic compounds in indoor air.
[0003] Existing air purifier filters mainly rely on the adsorption function of activated carbon particles in the carbon cloth material to purify gaseous pollutants in the air. Such filters will fail after adsorption saturation and may even cause secondary pollution to the use environment, so they need to be replaced regularly. Summary of the invention
[0004] The purpose of the present invention is to provide a double-effect carbon-containing cloth for an air purifier with a regeneration function and a preparation method thereof in order to overcome at least one of the defects of the above-mentioned prior art.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the purposes of the present invention is to provide a method for preparing a double-effect carbon cloth for an air purifier with a regeneration function, comprising the following steps:
[0007] S1, TiO2, K2CO3 and La(NO3)3 are mixed, calcined and immersed in a metal acid solution, taken out, dried and activated to obtain an exothermic material;
[0008] S2, ball-milling the exothermic material obtained in S1 until it is uniform, and then adding a dispersant to obtain an exothermic material spray liquid;
[0009] S3, spraying the exothermic material spray liquid obtained in S2 on one side of the receiving substrate multiple times to obtain an exothermic skeleton layer;
[0010] S4. The unsprayed surface of the exothermic skeleton layer obtained in S3 is sequentially laid with the first hot melt adhesive mesh, the first activated carbon layer, and the second hot melt adhesive mesh. After hot pressing and fixing, the second activated carbon layer, the third hot melt adhesive mesh, and the melt-blown cloth are sequentially laid, and hot pressing is performed to obtain a double-effect carbon-clamped cloth for an air purifier with a regeneration function.
[0011] Further, in S1, the Ti 2+ , K + and La3+ The molar ratio is (1~2):(5~7):(3~5).
[0012] Furthermore, in S1,
[0013] During the roasting process, the roasting temperature is 800-850°C and the roasting time is 1-2h;
[0014] During the impregnation process, the Pt + The concentration is 0.3wt%-5wt%, and the pH is 5.5-6.5;
[0015] During the impregnation process, ultrasonic waves are used to assist the impregnation, with the ultrasonic temperature being 45-55°C and the power being 30-40kHz;
[0016] During the drying process, the drying temperature is 110-120°C and the time is 6-8h.
[0017] Furthermore, in S1, the activation operation is: calcining the dried material at 500° C. for 2-4 h in an argon atmosphere with a heating rate of 5° C. / min.
[0018] Furthermore, in S3, the specific operation of spraying the exothermic material spray liquid on the receiving substrate multiple times is: spray the exothermic material spray liquid on the spraying surface of the receiving substrate through a sprayer, dry it at 70-110°C for 1-1.5h, and repeat the spraying multiple times so that the loading amount of the exothermic material on the receiving substrate is greater than 20%.
[0019] Furthermore, in S4, the activated carbon in the first activated carbon layer is selected to be dominated by mesopores and have a specific surface area of 800-1000m 2 / g, iodine value of 800-1000mg / g, 10wt% KOH impregnated alkaline activated carbon with a particle size of 0.25-0.60mm; the specific surface area of the activated carbon in the second activated carbon layer is selected to be 1300-1600m 2 / g, microporous coconut shell activated carbon with a particle size of 0.18-0.25mm and an iodine value of 1000-1500mg / g.
[0020] Furthermore, in S4, the amount of activated carbon in the first activated carbon layer is 150-200 g / m 2 The amount of activated carbon in the second activated carbon layer is 80-100 g / m 2 .
[0021] Further:
[0022] The receiving substrate has a gram weight of 70-90 g / m 2 Polyethylene terephthalate nonwoven fabric;
[0023] The first hot melt adhesive web and the third hot melt adhesive web are composed of one or more of polyolefin, copolyester and polyamide, with a melting range of 80-120°C and a gram weight of 10-15 g / m 2 ;
[0024] The second hot melt adhesive web is copolyester, with a melting range of 80-120°C and a gram weight of 18-25g / m 2 , wherein the copolyester preferably refers to polyethylene succinate (PES);
[0025] The meltblown fabric has a gram weight of 25 g / m 2 Polypropylene nonwoven.
[0026] Further, in S4, when laying the first activated carbon layer and the second activated carbon layer, a desktop conveyor is provided below the exothermic skeleton layer, and a high-voltage electrostatic powder spreader is provided above the exothermic skeleton layer to ensure that the activated carbon is evenly distributed on the exothermic skeleton layer;
[0027] The powder quantity adjustment range of the high-voltage electrostatic powder sprinkler is 25%-35%, and the conveying frequency of the desktop conveyor is set to 15-20Hz.
[0028] Furthermore, the hot pressing temperature ranges from 130 to 150°C.
[0029] The second object of the present invention is to provide a double-effect carbon cloth for an air purifier with a regeneration function, which is prepared by the preparation method as described above.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] (1) The air purification material of the present invention can be taken out after use and anhydrous ethanol can be sprayed on the spray skeleton layer to achieve material regeneration, which is convenient to operate and environmentally friendly. After ethanol is sprayed on the surface of the skeleton material, an exothermic reaction occurs under the catalytic action of the coating to generate CO2 and gaseous H2O. The generated heat is transferred to the chemical adsorption layer, the temperature rises, and the gaseous pollutants adsorbed in the activated carbon pores are desorbed, and the gas purification function of the air purification material is regenerated.
[0032] (2) The catalytic layer uses the heat released by the catalytic reduction reaction as a heat source. The catalytic layer is directly sprayed onto the receiving substrate. The receiving substrate has both support and heat conduction functions, which can effectively reduce the heat loss during the heat conduction process, so that more heat can be transferred to the adsorption layer, which can improve the regeneration rate. Compared with the metal wire mesh as a carrier and heat conduction layer, this material has a higher regeneration rate and better processability.
[0033] (3) The adsorption layer uses high iodine value activated carbon / modified carbon instead of ACF carbon cloth. Activated carbon has a rich pore structure. Activated carbon of the same gram weight has a higher adsorption capacity than ACF. The composite filter material has a lower pressure drop and higher particle efficiency while also reducing the cost of the filter material.
[0034] (4) The middle layer of the carbon cloth material of the present invention uses a PES hot melt adhesive mesh with high rigidity and high toughness. The PES adhesive mesh can maintain stable mechanical properties while being hot-pressed and flow-formed, and has excellent strength and rigidity. It enhances the stiffness of the carbon cloth material while also allowing certain gaps in the activated carbon layer, thereby increasing the effective contact area between the gas and the activated carbon layer and reducing the filtration resistance of the carbon cloth material to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is the toluene adsorption performance curve of the purification material sample of Example 1;
[0036] Figure 2 is the sulfur dioxide adsorption performance curve of the purification material sample of Example 1;
[0037] Figure 3 is the resistance variation curve of the purification material sample of Example 1;
[0038] Figure 4 This is the toluene adsorption performance curve of the purification material sample of Comparative Example 1;
[0039] Figure 5 This is the toluene adsorption performance curve of the purification material sample of Example 3. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0041] Example 1
[0042] This embodiment provides a double-effect carbon cloth for an air purifier with a regeneration function, comprising a superimposed exothermic skeleton layer and a chemical adsorption layer, which is prepared by the following steps:
[0043] Step 1: Preparation of exothermic skeleton layer
[0044] (1) Weigh Ti 2+ :K + :La 3+After the TiO2 / K2CO3 / La(NO3)3 with a molar ratio of 1.5:6:4 is mixed evenly, the mixture is placed in a mortar and ground until the materials are evenly mixed and the particles are fine. The powder is transferred to an alumina crucible and baked in a muffle furnace at 800°C for 2h.
[0045] (2) preparing a 0.3 wt % chloroplatinic acid aqueous solution as an impregnation solution, immersing the above-mentioned material carrier in the chloroplatinic acid impregnation solution, and controlling the pH value at 5.5-6.5; ultrasonic temperature 45° C., power 30 kHz; taking out the material after it is soaked until there is no color change, drying it at 120° C. for 8 h, and then transferring it to a tube furnace and calcining it at 500° C. for 4 h under an Ar atmosphere to obtain an exothermic material; mixing 10 parts by weight of the exothermic material, 1 part of polyvinyl alcohol and 20 parts of 0.5 mol / L nitric acid solution, adding nitric acid to adjust the pH value to 6, forming a slurry by ball milling, and measuring the slurry D90 = 102 nm by particle size distribution instrument analysis to obtain an exothermic material spray liquid, which is transferred to a sprayer for standby use;
[0046] (3) The receiving substrate weight is 70-90g / m 2 The polyethylene terephthalate non-woven fabric is fixed on the desktop with the sprayed surface facing up, a protective film is stacked on the unsprayed surface, and the skeleton surface is sprayed with a spray pump. After spraying, the receiving substrate is transferred to an oven at 70°C and dried for 1h. The above spraying and drying operations are repeated 3 times. The coating loading is 20% by weighing and calculating, and the heat-releasing skeleton layer can be obtained.
[0047] Step 2: Preparation of double-effect carbon cloth for air purifier with regeneration function
[0048] (1) laying a first hot melt adhesive mesh on the unsprayed layer of the heat-releasing skeleton layer receiving substrate and hot pressing and fixing it, then evenly laying a first activated carbon on the surface, laying a second layer of adhesive mesh on the first activated carbon layer and hot pressing and fixing it, and then sprinkling the second activated carbon on the mesh, then laying a third layer of hot melt adhesive mesh on the second activated carbon, and then stacking a melt-blown cloth on the third hot melt adhesive mesh,
[0049] The hot pressing temperature is controlled at 130°C; the first activated carbon is selected with a pore structure dominated by mesopores and a specific surface area of 800m 2 / g, iodine value of 800mg / g, particle size of 0.45-0.60mm and alkaline activated carbon impregnated with 10wt% KOH; the second activated carbon is selected with a specific surface area of 1500m 2 / g, particle size 0.20-0.25mm, iodine value of 1500mg / g microporous coconut shell activated carbon; the laying amount of the first activated carbon and the second activated carbon is 150g / m 2 , 80g / m 2 ; Meltblown fabric layer uses 25g / m 2Polypropylene (PP) meltblown nonwoven fabric; the first and third hot melt adhesive webs are 10g / m 2 The melting temperature of polyolefin (PO) is 95-105℃; the second hot melt adhesive web is 15g / m 2 copolyester (PES).
[0050] (2) A desktop conveyor is set below the aggregate and a high-voltage electrostatic powder sprinkler is set above it to ensure that the activated carbon can be evenly distributed in the skeleton layer. The speed frequency of the desktop conveyor is 15 Hz;
[0051] (3) The above-mentioned sequentially stacked materials are pressed and formed by hot pressing to obtain a renewable carbon cloth material, wherein the hot pressing temperature is controlled at 130° C.
[0052] The carbon cloth material prepared above was cut into a disc filter material with a diameter of 112.9 mm and applied to the toluene gas filtration treatment test. The toluene concentration was 80 ppm (air as the bottom gas), the surface wind speed was 0.1 m / s (the aggregate surface was facing the wind), the experimental environment was: temperature 25 ° C, relative humidity 50%, the toluene removal efficiency at 5 min and 10 min, and the toluene removal efficiency change curve with time was shown in Figure 1 middle.
[0053] The carbon cloth material prepared above was cut into a disc filter material with a diameter of 112.9 mm and applied to the SO2 gas filtration treatment test. The SO2 concentration was 80 ppm (air as the bottom gas), the surface wind speed was 0.1 m / s (the aggregate surface was facing the wind), the experimental environment was: temperature 25 ° C, relative humidity 50%, the SO2 removal efficiency at 5 min and 10 min, and the change curve of SO2 removal efficiency over time was presented in Figure 2 middle.
[0054] The carbon cloth prepared above was taken and made into filters through folding and gluing processes. 3 / h、250m 3 / h test its pressure drop. Experimental environment: temperature 25℃, relative humidity 50%, filter pressure drop under different air volume Figure 3 shown.
[0055] The carbon-clad cloth material prepared above was used to test its pressure drop and particle efficiency (@32LPM) using TSI8130A, its thickness using a fabric thickness tester, and its bending stiffness using a bending stiffness tester. The experimental environment: temperature 25°C, relative humidity 50%. The relevant physical property data are shown in Table 1.
[0056] The above-mentioned air purification material after use was taken out, and 11.2mL of anhydrous ethanol was evenly sprayed on the skeleton surface. After spraying, it was placed vertically on the table for 30 minutes, and then put back on the fixed bed for testing again. This "regeneration-test" was repeated 3 times. During the regeneration process, the temperature of the sample skeleton surface can reach up to about 65°C, and the desorbed toluene concentration can be detected by a handheld VOC detector up to 400ppm.
[0057] The performance results of the material after each regeneration for adsorption of toluene are presented in Figure 1 It can be seen that the initial efficiency of the filter material drops to about 95% after regeneration once. This is because at the exothermic temperature, the toluene molecules in the activated carbon pores can only be partially desorbed, and a small amount of toluene is still adsorbed inside the material. After two and three regenerations, the toluene adsorption performance of the material is basically the same as that of the regeneration once, which shows that the air purification material has a better recovery of adsorption performance after regeneration. And after three regenerations, the material is firmly connected without delamination or separation.
[0058] Comparative Example 1
[0059] Compared with Example 1, the difference is that in step 1, the heating layer material is not impregnated with chloroplatinic acid aqueous solution, but directly activated, and the rest remains unchanged.
[0060] After step 3, the prepared carbon cloth material was taken and cut into a disc filter material with a diameter of 112.9 mm, which was applied to the toluene gas filtration treatment test. The toluene concentration was 80 ppm (air as the bottom gas), the surface wind speed was 0.1 m / s (the aggregate surface was facing the wind), and the experimental environment was: temperature 25 ° C, relative humidity 50%, the toluene removal efficiency and toluene adsorption capacity at 5 min and 10 min (the toluene concentration downstream of the filter material reached 95% of the upstream concentration) are listed in Table 1, and the toluene removal efficiency over time is shown in Table 1. Figure 4 middle.
[0061] The above-mentioned air purification material after use was taken out, and 11.2mL of anhydrous ethanol was used to spray evenly on the skeleton layer. After spraying, it was placed vertically on the table for 30 minutes, and then put back on the fixed bed for testing again. This "regeneration-test" was repeated 3 times. During the regeneration process, the maximum temperature of the sample skeleton surface was about 40°C, and the desorbed toluene concentration could be detected up to 200ppm using a handheld VOC detector.
[0062] The presence of Pt active sites can increase the migration rate of photoelectrons and increase the effective exothermic reaction. The catalytic exothermic effect of the coating is worse, and the adsorption layer is not fully desorbed from toluene. The regenerated material is put back into the fixed bed and retested. The toluene adsorption performance is weakened, and the regeneration is poor.
[0063] Comparative Example 2
[0064] Compared with Example 1, in step 2, the air purification material after use is taken out, and 11.2 mL of 75% ethanol is used to evenly spray the skeleton layer. After spraying, it is placed vertically on the table for 30 minutes, and then put back into the fixed bed for testing again. This "regeneration-test" is repeated 3 times, and the rest remains unchanged.
[0065] After step 3, the prepared carbon cloth material is taken, cut into a disc filter material with a diameter of 112.9 mm, and applied to the toluene gas filtration treatment test, the toluene concentration is 80 ppm (air is the bottom gas), the surface wind speed is 0.1 m / s (the aggregate surface faces the wind), the experimental environment: temperature 25 ° C, relative humidity 50%, the toluene removal efficiency and toluene adsorption capacity at 5min and 10min are shown in Table 1 (the toluene concentration downstream of the filter material reaches 95% of the upstream concentration), and the above-mentioned air purification material after use is taken out and regenerated. During the regeneration process, the surface temperature of the sample aggregate can reach up to about 50 ° C. The desorbed toluene concentration can be detected by a handheld VOC detector up to 200 ppm. This is because water molecules and ethanol are competitively adsorbed on the surface of the regenerated material. The presence of water molecules will weaken the exothermic reaction of the regenerated material, thereby making the adsorption layer desorb toluene insufficient. The regenerated material is put back into the fixed bed and retested for toluene adsorption performance, which is weakened and has poor reproducibility.
[0066] Comparative Example 3
[0067] Compared with Example 1, the difference is that in step 2, the laying amount of the first and second activated carbons is 200 g / m 2 , 100g / m 2 , the rest remain unchanged.
[0068] After step three, the prepared carbon cloth material is taken out, cut into a disc filter material with a diameter of 112.9 mm, and applied to the toluene gas filtration treatment test. The toluene concentration is 80 ppm (air is the bottom gas), the surface wind speed is 0.1 m / s (the aggregate surface faces the wind), and the experimental environment is: temperature 25°C, relative humidity 50%, and the toluene removal efficiency and adsorption capacity at 5min and 10min are shown in Table 1. The air purification material that has failed to be used is taken out and regenerated, and the operation is repeated 3 times. The material after each regeneration is tested for toluene adsorption performance, and the results are as follows Figure 5 It shows that compared with the initial sample, the adsorption efficiency of the first regenerated material is poor. This is because the carbon cloth filter material layer is thicker, and the heat generated by the skeleton layer cannot be transferred to the entire activated carbon layer, causing the regeneration performance to decline.
[0069] Comparative Example 4
[0070] Compared with Example 1, the difference is that the activated carbon in step 2 is replaced with activated carbon fiber ACF of the same gram weight, and the rest remains unchanged.
[0071] After step 3, the prepared carbon cloth material was taken, and its pressure drop and particle efficiency (@32LPM) were tested using TSI8130A, its thickness was measured using a fabric thickness tester, and its bending stiffness was measured using a bending stiffness tester. The results are shown in Table 1. Compared with the sample in Example 1, the resistance and thickness of the sample increased significantly. This is because compared with activated carbon, the ACF of the same gram weight has higher resistance and thickness, which also makes the sample in Comparative Example 4 have a slower efficiency in gas adsorption.
[0072] Comparative Example 5
[0073] Compared with Example 1, the difference is that in step one, the catalytic layer is sprayed onto the metal mesh, and then the adsorption layer and the metal mesh are hot-pressed into shape in sequence, and the rest remains unchanged.
[0074] After step 3, the prepared carbon cloth material was taken and its pressure drop and particle efficiency (@32LPM) were tested using TSI8130A, its thickness was measured using a fabric thickness tester, and its bending stiffness was measured using a bending stiffness tester. The results are shown in Table 2. Compared with the sample in Example 1, the resistance of the sample is reduced. Due to the presence of the metal wire mesh, the stiffness of the filter material is greatly increased, and the subsequent processability is poor.
[0075] Table 1 Toluene adsorption efficiency
[0076]
[0077]
[0078] Table 2 Physical properties
[0079] Resistance / pa efficiency Thickness / mm Push force / mN Example 1 26 99.1% 1.60 67.332 Comparative Example 4 40 99.0% 2.10 74.491 Comparative Example 5 24 98.0% 1.65 98.807
[0080] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a double-effect carbon cloth for an air purifier with a regeneration function, characterized in that: The steps include: S1, TiO2, K2CO3 and La(NO3)3 are mixed, calcined and immersed in a metal acid solution, taken out, dried and activated to obtain an exothermic material; S2, ball-milling the exothermic material obtained in S1 until it is uniform, and then adding a dispersant to obtain an exothermic material spray liquid; S3, spraying the exothermic material spray liquid obtained in S2 on one side of the receiving substrate multiple times to obtain an exothermic skeleton layer; S4. The unsprayed surface of the exothermic skeleton layer obtained in S3 is sequentially laid with the first hot melt adhesive mesh, the first activated carbon layer, and the second hot melt adhesive mesh. After hot pressing and fixing, the second activated carbon layer, the third hot melt adhesive mesh, and the melt-blown cloth are sequentially laid, and hot pressing is performed to obtain a double-effect carbon-clamped cloth for an air purifier with a regeneration function.
2. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S1, the Ti 2+ , K + and La 3+ The molar ratio is (1~2):(5~7):(3~5).
3. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S1, During the roasting process, the roasting temperature is 800-850°C and the roasting time is 1-2h; During the impregnation process, the Pt + The concentration is 0.3wt%-5wt%, and the pH is 5.5-6.5; During the impregnation process, ultrasonic waves are used to assist the impregnation, and the ultrasonic temperature is 45-55°C and the power is 30-40kHz; During the drying process, the drying temperature is 110-120°C and the time is 6-8h.
4. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S1, the activation operation is: calcining the dried material at 500°C for 2-4h in an argon atmosphere with a heating rate of 5°C / min.
5. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S3, the specific operation of spraying the exothermic material spray liquid on the receiving substrate multiple times is: spray the exothermic material spray liquid on the spraying surface of the receiving substrate through a sprayer, dry it at 70-110°C for 1-1.5h, and repeat the spraying multiple times to make the loading amount of the exothermic material on the receiving substrate greater than 20%.
6. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S4, the specific surface area of the activated carbon in the first activated carbon layer is 800-1000m 2 / g, iodine value of 800-1000 mg / g, and particle size of 0.25-0.60 mm, and is alkaline activated carbon impregnated with 10wt% KOH.
7. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S4, the specific surface area of the activated carbon in the second activated carbon layer is selected to be 1300-1600m 2 / g, microporous coconut shell activated carbon with a particle size of 0.18-0.25mm and an iodine value of 1000-1500mg / g.
8. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: In S4, the amount of activated carbon laid in the first activated carbon layer is 150-200 g / m 2 The amount of activated carbon in the second activated carbon layer is 80-100 g / m 2 .
9. The method for preparing a double-effect carbon cloth for an air purifier with a regeneration function according to claim 1, characterized in that: The receiving substrate has a gram weight of 70-90 g / m 2 Polyethylene terephthalate nonwoven fabric; The first hot melt adhesive web and the third hot melt adhesive web are composed of one or more of polyolefin, copolyester and polyamide, with a melting range of 80-120°C and a gram weight of 10-15 g / m 2 ; The second hot melt adhesive web is copolyester, with a melting range of 80-120°C and a gram weight of 18-25g / m 2 ; The meltblown cloth has a gram weight of 20-30 g / m 2 Polypropylene nonwoven fabric, preferably 25g / m 2 Polypropylene nonwoven.
10. A double-effect carbon cloth for an air purifier with regeneration function, characterized in that: The invention discloses a novel nanostructured carbon foam prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Flame-retardant activated carbon for adsorbing ammonia gas and preparation method of flame-retardant activated carbon
CN114682213A
Renewable air purification material as well as preparation method and regeneration method thereof
CN115920882A
Cyclic Adsorptive Reactor and Method for Valorizing CO2 / CH4 Mixtures
PT117138A
Cited By
Deodorizing material and preparation method thereof
CN121266352A
Deodorizing material and method for preparing the same
CN121266352B
